Privacy Preserved Cyber-Physical Searching for Information-Centric Intelligent Agriculture - Li Ding (IEEE, 2021)
Technological evolution has brought great changes to traditional industries. Nowadays farmers obtain great benefits such as intelligent production and convenient management from intelligent agriculture. Nevertheless, there still exists many flaws in current solutions. Deficiencies in energy management, data transmission and privacy preservation are supposed to be solved. In this paper, the privacy preserved cyber-physical searching framework is proposed to tackle these problems. This four-layer framework can provide a convenient way for farmers to manage production by simply searching for information they interested in. The data source layer contains many sensors for data collection. The data aggregation layer consists of data aggregation nodes deployed in the farms. The data transfer layer employs drones for retrieving data from data aggregation nodes. The cloud control layer is responsible for searching requests processing and privacy preservation. To realize better data collection and searching. The information centric network is introduced into this framework. Moreover, some methods are employed for privacy preservation. The simulation results show the feasibility of this framework.